2021
DOI: 10.1108/bjm-09-2020-0341
|View full text |Cite
|
Sign up to set email alerts
|

Goal clarity as a link between humble leadership and project success: the interactive effects of organizational culture

Abstract: PurposeUsing the lens of conservation of resources (COR) theory, the purpose of this paper is to explore the effect of humble leadership on project success by integrating the mediating role of goal clarity. The authors also argue that organizational culture moderates these direct and indirect relationships through goal clarity.Design/methodology/approachTime-lagged data were collected from 329 employees in the civil construction sector of Pakistan.FindingsThe results indicate that humble leadership enhances pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Prior literature suggests that humble leadership is vital for workplace outcomes, such as team effectiveness and project outcomes [37,38]. Still, project leadership work remains relatively scarce [5,39] and humble project managers in a project context may vary substantially, compared to permanent organisations [40].…”
Section: Humble Leadership and Project Management Effectivenessmentioning
confidence: 99%
“…Prior literature suggests that humble leadership is vital for workplace outcomes, such as team effectiveness and project outcomes [37,38]. Still, project leadership work remains relatively scarce [5,39] and humble project managers in a project context may vary substantially, compared to permanent organisations [40].…”
Section: Humble Leadership and Project Management Effectivenessmentioning
confidence: 99%
“…The person-role conflict (r = 0.13, p < 0.05) tended to be higher among married workers. Although it is evident from Table 1 that gender is insignificant in correlation with emotional exhaustion and psychological capital, we still conducted an independent sample T-test on both constructs' scores to check the mean differences between males and females (Hameed et al, 2015;Ali et al, 2021). Results showed that gender Exhausting job demand to satisfy difference with respect to emotional exhaustion (t = 1.2, p > 0.05) and psychological capital (t = À1.9, p > 0.05) was insignificant…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PLS-SEM permits the complex configurational mode of HRM practices that captures the synergistic results taking higher-order constructs (HOCs), which are not found in covariance-based SEM (Ringle et al, 2020). Additionally, PLS-SEM has been utilized across a wide range of inter-related social science scholarly work, including leadership (Ali et al, 2021), entrepreneurship (Ziyae and Sadeghi, 2020), informational technology (Leong et al, 2020;Tan et al, 2019), human resource management (Ringle et al, 2020) and tourism (Fam et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…, 2020). Additionally, PLS-SEM has been utilized across a wide range of inter-related social science scholarly work, including leadership (Ali et al , 2021), entrepreneurship (Ziyae and Sadeghi, 2020), informational technology (Leong et al. , 2020; Tan et al , 2019), human resource management (Ringle et al.…”
Section: Methodsmentioning
confidence: 99%